STRATEGI PEMASARAN BISNIS MENGGUNAKAN INFLUENCER MELALUI MEDIA SOSIAL INSTAGRAM - azhar (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
Culinary Business Marketing Strategy Using Influencers Through Instagram Social Media (Case Study on apety shop). This type of research uses primary data and secondary data using a qualitative research design. The number of informants in this research was 6 people (1 Owner and 5 Visitors). The sample will be obtained using purposive sampling technique. Data collection techniques can be carried out by means of interviews, and observations, and a combination of the three, directly from respondents selected as samples, which includes the respondent's identity data. Based on the results obtained using qualitative analysis, it can be concluded in this research that the reason why the marketing strategy switched from conventional methods to Instagram marketing is, firstly because of technological advances, consumers are more inclined to use Instagram social media, secondly by using social media. marketing media, especially Instagram, can further reduce costs in marketing financing. Third, by utilizing influencers, it can further improve marketing on Instagram, and have a positive impact on the progress . Lastly, the role of the variable place in the marketing mix can make visitors come back. because spices provide and present an attractive interior and atmosphere for consumers and the prices are also in line with consumers' pockets. A place that according to researchers is less strategic, but with advances in technology and promotional strategies for Itta Kitchen Spices, it can immediately reach the hearts of consumers.